Carotid Doppler Ultrasonography in Patients with Co-existing Type 2 Diabetes Mellitus and Hypertension in Nigeria - Adekoya AO; Olatunji AA; Akinola AR; Odusan O; Adekoya AO; Olawale OO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: The co-existence of diabetes mellitus (DM) and hypertension (HTN) has been rising globally with subclinical atherosclerotic complications. These vascular changes can be detected using carotid ultrasonography. Objectives: To determine and compare the carotid arterial structural wall changes and blood flow velocities of adults with co-existing DM and HTN with age- and sex-matched non-diabetic, non-hypertensive controls. Methods: A cross-sectional comparative study of 300 participants comprising 200 adults with co-existing DM and HTN and 100 age- and sex-matched controls was done. Their carotid arteries were examined bilaterally for plaques, carotid intima media thickness (CIMT) and flow velocities - peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI) and resistive index (RI) using 4-12MHz linear array transducer. Visceral obesity and serum lipids were also assessed. Results: The mean age of the subjects was 56.13 ± 6.93 years; they comprised 38% males and 62% females. The subjects' CIMT was statistically significantly higher (p = 0.001) with a three-fold mean increase (45.5%) compared to the controls (13.7%). Lower flow velocities but higher indices were also observed in the subjects. Strong and significant correlations were observed between EDV and PI (r =-0.663, p =>0.001), EDV and RI (r = -0.661, p =>0.001) and PI and RI (r =0.988, p = >0.001) among the subjects. Conclusion: Significant reduction in flow velocities with increased CIMT may be an early indication of subclinical atherosclerosis. Therefore, carotid ultrasonography should be mandatory in individuals at risk for early detection and possible prevention of atherosclerotic complications.